Some behavioural aspects on the Hemidactylus species of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Hemidactylus is a taxonomically complex genus and little is known about its feeding and breeding behavior in Bangladesh. Most of the species of this genus have a preference to live within human habitations, and play an important role in ecosystem, controlling insect pest population. Their breeding strategy is almost similar with each other and associated with their body structure. Review of literature found that there is a relationship between life history pattern and their reproductive biology. They lay two eggs per clutch usually and the highest egg number (12) has been recorded for H. frenatus. Strong significant positive correlation (r = 0.91) was found for preclaocal-femoral pores and egg number. Besides, significant negative correlation was found for average female body size and egg number (r = 0.96). Previous work and observation records showed that feeding habit is almost similar among all species of Hemidactylus and dipteran insects were the mostly consumed food item.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 77-84